lncRNA MEG3 Suppresses the Progression of Ankylosis Spondylitis by Regulating the Let-7i/SOST Axis - Ma, Junjie; Zhang, Xiaohua; Zhang, Hongxing; Chen, Hailong (Frontiers in Molecular Biosciences, 2020)
Ankylosis spondylitis (AS) is a disease mainly characterized by sacroiliac joint and spinal attachment point inflammation. Long non-coding RNA (lncRNA) plays a key role in the progression of many diseases. However, few studies have been conducted on the function of lncRNA maternally expressed gene 3 (MEG3) in AS. Quantitative real-time polymerase chain reaction (qRT-PCR) was used to measure the relative levels of MEG3, microRNA let-7i, sclerostin (SOST), and inflammatory cytokines. Dual-luciferase reporter assay, RNA immunoprecipitation (RIP) assay and biotin-labeled RNA pull-down assay were used to confirm the interaction between MEG3 and let-7i or let-7i and SOST. In addition, western blot (WB) analysis was performed to detect the protein levels of osteogenesis markers and SOST. The expression levels of MEG3 and SOST were decreased and let-7i was increased in AS patients. MEG3 could interact with let-7i in AS fibroblasts, and let-7i overexpression reversed the suppressive effect of MEG3 upregulation on the inflammation and bone formation of AS. Additionally, let-7i could target SOST, and SOST silencing reversed the inhibitory effect of let-7i inhibitor or MEG3 overexpression on the inflammation and bone formation of AS. Furthermore, SOST expression was positively regulated by MEG3, while was negatively regulated by let-7i. Our results revealed that lncRNA MEG3 promoted SOST expression to restrain the progression of AS by sponging let-7i, which provided a treatment target for AS.